Investigation of the effect on the mortality of the brine shrimp nauplii Artemia salina L. and the antiproliferative activity of thyme essential oil - Korić, Emina; Nikšić, Haris; Gušić, Irma; Durić, Kemal (Archives of Pharmacy, 2022)
The aim of this work was to examine the effect of the essential oil of the aerial blooming parts of thyme, Thymus vulgaris L. on the mortality of the brine shrimp nauplii Artemia salina L. in vivo and to evaluate the antiproliferative activity on selected tumor cell lines in vitro. An in vivo assay was performed using the Brine Shrimp Lethality Test (BSLT). In vitro evaluation of antiproliferative activity was performed on three human tumor cell lines: breast adenocarcinoma MCF-7, lung carcinoma H460 and acute lymphoblastic leukemia MOLT-4 using the MTT assay. The essential oil components thymol (36.7%), p-cymene (30.0%), γ-terpinene (9.0%) and carvacrol (3.6%) were identified and quantified by gas chromatography/mass spectrometry. In the BSLT assay, thyme essential oil showed high toxicity to brine shrimp nauplii (LC50 60.38 µg/mL), in accordance with the cytotoxicity evaluation criteria. Inhibition of tumor cell proliferation in vitro was concentration-dependent. The hematological tumor cell line MOLT-4 was less sensitive to the tested essential oil than the solid tumor cell lines MCF-7 and H460, with IC50 values ​​of 228.78 µg/mL for MOLT-4, 68.59 µg/mL for H460 and 52.65 µg/mL for MCF-7. A good correlation between the IC50 values ​​in BSLT assay and the LC50 values in MTT assay for human solid tumors was established.